2012
DOI: 10.1186/1471-2407-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Metformin efficacy and safety for colorectal polyps: a double-blind randomized controlled trial

Abstract: Background Colorectal cancer is one of the major neoplasms and a leading cause of cancer death worldwide, and new preventive strategies are needed to lower the burden of this disease. Metformin, a biguanide, which is widely used for treating diabetes mellitus, has recently been suggestive to have a suppressive effect on tumorigenesis and cancer cell growth. In a previous study conducted in non-diabetic subjects, we showed that oral short-term low-dose metformin suppressed the development of colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…These effects are particularly intriguing for CRC because Peutz-Jeghers polyposis involves loss of LKB1, a tumor suppressor that also regulates AMPK. Metformin also appears to inhibit polyp formation and aberrant crypt foci (4042). …”
Section: Discussionmentioning
confidence: 99%
“…These effects are particularly intriguing for CRC because Peutz-Jeghers polyposis involves loss of LKB1, a tumor suppressor that also regulates AMPK. Metformin also appears to inhibit polyp formation and aberrant crypt foci (4042). …”
Section: Discussionmentioning
confidence: 99%
“…Other high-risk groups include patients with premalignant conditions such as colorectal polyps or Barrett's esophagus. Indeed, a multicenter double-blind placebo-controlled randomized trial of metformin in the prevention of colorectal polyps in nondiabetic patients is currently under way (72). If proven effective, metformin will be an attractive anticancer agent because of its safety, tolerability, and widespread availability, but further investigation into the effects of metformin are required to properly assess its potential in oncology.…”
Section: Future Directionsmentioning
confidence: 98%
“…In vitro study has also demonstrated growth inhibitory effects of metformin in colon cancer cells via activating AMP-activated protein kinase (AMPK) pathway (12). Furthermore, in clinical trials, metformin suppressed colonic epithelial proliferation and rectal ACF formation in humans (13, 14). It is hypothesized that metformin has both direct and indirect anti-neoplastic actions.…”
Section: Introductionmentioning
confidence: 99%